Effect of microstructural evolution on wettability and tribological behavior of TiO2 nanotubular arrays coated on Ti–6Al–4V. Issue 6 (July 2015) - Sarraf, M.; Zalnezhad, E.; Bushroa, A.R.; Hamouda, A.M.S.; Rafieerad, A.R.; Nasiri-Tabrizi, B.
Abstract: Self-organized TiO2 nanotubular arrays were fabricated by electrochemical anodization of Ti–6Al–4V plates in an NH4 F/H3 PO4 electrolyte. The effect of microstructural evolutions on the wettability and tribological behavior of the TiO2 nanotubes was investigated. Based on the XRD profiles of the fabricated material, the characteristic TiO2 peaks were not recognized after anodization; however, highly crystalline TiO2 (anatase and rutile) was formed due to crystallization during annealing at 500 °C for 1.5 h. The nanotube arrays were converted entirely to rutile at 700 °C. From a microstructure point of view, a highly ordered nanotube structure was achieved when the specimen was annealed at 500 °C, with a length of 0.72 μm and a pore diameter of 72 nm. Further increasing the annealing temperature to 700 °C resulted in the complete collapse of the tubular structure. The results indicate that the improved wettability of the anodized specimens was due to the combination of the effects of both the surface oxide layer and the increased surface roughness achieved after anodization. Moreover, the wear resistance and wettability of the sample annealed 500 °C were improved due to the high hardness (435 HV) and low coefficient of friction (0.133–168) of the highly crystalline structure of the TiO2 nanotubes.